Translocation efficiencies and allocation of nitrogen, phosphorous and potassium in rice as affected by silicon fertilizer under high daytime temperature. (29th October 2018) - Liu, Qihua; Ma, Hui; Sun, Zhaowen; Lin, Xiangqing; Zhou, Xuebiao
Abstract: High temperature has become a bottleneck limiting rice production in many rice‐growing districts. Silicon is considered as a beneficial element for rice development, being involved in mitigating adversity stress. In order to ascertain how high temperature and silicon affect nitrogen (N), phosphorous (P) and potassium (K) translocation efficiencies and allocation in rice plants, a field experiment with split plot design was conducted in two consecutive years. Silicon fertilizer treatments, including applying silicon fertilizer and without applying silicon fertilizer, were regarded as main plots. Temperature treatments, including high daytime temperature (HDT) and normal temperature (NT), were assigned as subplots. The results indicated that, as compared to NT, HDT reduced the translocation efficiencies of N, P and K in leaves and stems plus sheaths except for the K translocation efficiency in stems plus sheaths. Moreover, HDT decreased grain yield and the allocation rates of N, P and K in panicles at maturity. Under HDT, the application of silicon fertilizer obviously enhanced the N translocation efficiency of leaves and stems plus sheaths, and the K translocation efficiency of leaves. The application of silicon fertilizer increased grain yield and the allocation rates of N and K in panicles at maturity under HDT. Correlation analysis showed that rice grain yield was positively significantly correlated with N, P and K translocation efficiencies of leaves and their allocation rates in panicles at maturity. Conversely, grain yield was negatively related to the N and P allocation rates in leaves and stems plus sheaths at maturity. These results imply that HDT generated adverse effect on the translocation efficiency of nutrition in rice plants, which might be another damage induced by high temperature to the formation of rice grain yield. Additionally, silicon fertilizer could play a key role in positively regulating the N and K translocation efficiencies and allocation rates in rice under HDT.